Determination of an effective pore dimension for microporous media. (October 2019) - Johansson, M.V.; Testa, F.; Perrier, P.; Vicente, J.; Bonnet, J.P.; Moulin, P.; Graur, I.
Highlights: The measured mass flow rate through a microporous media is analyzed in the frame of a bundle of capillaries model. The effective pore size, an intrinsic property of the porous media, is extracted. The sample porosity, the tortuosity and the internal surface are also calculated. The extracted properties are compared with the results of microtomography and mercury porosimetry. Abstract: The transient method of the mass flow rate and permeability measurements through a microporous media, developed previously, is used here to extract different characteristics of the media. By implementing the model of porous media as a bundle of capillaries the effective pore dimension is extracted from the measurements, and its physical interpretation is given. This methodology shows promising results to be used as a non-destructive method of micro-and-nanoporous media analysis. The permeability is also extracted directly from the measurements of the pressure variation in time. By using additional information about the sample porosity, the number of capillaries, the tortuosity and the internal surface of the sample are calculated. The extracted values are very close to that obtained by the mercury porosimetry and by microtomography.